Strengthening Market Position And Offerings For Bagus Agro Pelaga In Competitive Hospitality Industry - Niña Jesha D. Clacio; Camela Erika D. Baltazar-Dayonot; Wilmer Jane A. Lustan; Stephanie B. Virtus-Reyes; Hanilyn Aguilar Hidalgo; Ida Bagus Udayana Putra; Ida Ayu Surasmi; Genijayendra Sahya Amertha; Putu Arika Wandari (Universitas Warmadewa, 2024)
The purpose of this research is to analyze and enhance the market positioning of Bagus Agro Pelaga, a wellness farm resort and lifestyle retreat in Bali, Indonesia, within the competitive hotel industry. This study employs a qualitative research design to assess and evaluate the current business environment and organizational systems. A case study approach is used, allowing for an in-depth investigation of the resort over a specific period. Data collection involved personal interviews with Mr. Taufik, the head of the marketing department of Bagus Discovery Group, along with observations, document analysis, and customer reviews. The research also incorporated secondary and historical financial and marketing data to provide a comprehensive understanding of the resort's situation before, during, and after the pandemic. SWOT Analysis principles were applied to analyze the resort's strengths, weaknesses, opportunities, and threats, forming the basis for strategic recommendations. The findings revealed three main challenges: a manpower shortage due to an aging workforce, difficulty adopting new technologies, and poorly maintained facilities. These issues were analyzed for their impact on operations and customer experience. The study recommends developing a comprehensive workforce development plan, investing in technology upgrades and staff training, and prioritizing resource allocation for facility maintenance and improvements. By addressing these challenges, Bagus Agro Pelaga can enhance its market positioning, attract more visitors, and achieve long-term sustainability.